2015
DOI: 10.17795/nmsjournal28332
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Using Eye Mask on Sleep Quality in Cardiac Patients: A Randomized Controlled Trial

Abstract: Background:Patients in coronary care unit are at risk of sleep deprivation. Sleep deprivation can be associated with increased blood pressure and heart rate, raising the risk of developing cardiovascular problems among patients hospitalized in coronary care unit.Objectives:This study was carried out to examine the effect of eye mask on sleep quality in cardiac patients.Patients and Methods:In this randomized controlled trial, 60 patients who met the inclusion criteria were selected using a convenient sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1
10

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(45 citation statements)
references
References 11 publications
2
32
1
10
Order By: Relevance
“…Three authors (Babaii et al ., ; Daneshmandi et al ., ; Neyse et al ., ) used the Pittsburgh Sleep Quality Index (PSQI). The first study confirmed statistically significant differences in five of the seven monitored domains ( P < 0.05), the second study confirmed a significant improvement in sleep quality after intervention in the total sleep quality score (10.46 ± 4.09/4.86 ± 1.88, P < 0.000) and the third study was in agreement with the results of the second study with the total sleep quality score (10.3 ± 6.3/6.3 ± 2.1, P < 0.001).…”
Section: Results and Analysismentioning
confidence: 99%
“…Three authors (Babaii et al ., ; Daneshmandi et al ., ; Neyse et al ., ) used the Pittsburgh Sleep Quality Index (PSQI). The first study confirmed statistically significant differences in five of the seven monitored domains ( P < 0.05), the second study confirmed a significant improvement in sleep quality after intervention in the total sleep quality score (10.46 ± 4.09/4.86 ± 1.88, P < 0.000) and the third study was in agreement with the results of the second study with the total sleep quality score (10.3 ± 6.3/6.3 ± 2.1, P < 0.001).…”
Section: Results and Analysismentioning
confidence: 99%
“…Since light exposure appeared to be the main culprit, we believe that the intervention to reduce light exposure is very important in order to improve sleep quality in hospitalized patients. Previous studies demonstrated the effectiveness of using eye mask in improving sleep quality in hospitalized patients in general medical wards, post anesthesia care units as well as in intensive care units [33][34][35]. A review also demonstrated that changing the sound and light environment appeared to be effective in improving sleep in hospitals [36].…”
Section: Sleep Disordersmentioning
confidence: 99%
“…Uygulaması kolay ve etkin olan, bireye ekonomik yük getirmeyen nonfarmakolojik yöntemlerin uyku sorunlarını azaltmada etkili olabileceğini gösteren kanıtlar bulunmaktadır. [22][23][24][25][26][27][28][38][39][40][41][42][43][44][45][46] KY olan hastalarda nonfarmakolojik yöntemlerin uyku kalitesine etkisini inceleyen çalışmaların özellikleri tablo 1'de verilmiştir. [38] destekleyici eğitim [38] Çevrenin düzenlenmesi: Gürültü ve ışık gibi faktörleri ortadan kaldırarak hasta birey için dinlendirici bir ortam hazırlamak ve çevre düzenini sağlamak, uyku ve diğer temel fizyolojik gereksinimlerinin yerine getirilmesine yardımcı olmak hemşirelerin temel görevlerinden biridir.…”
Section: Kalp Yetersizliği Hastalarında Uyku Sorunlarının Giderilmesiunclassified
“…Müdahale grubunun %23'ünü KY hastalarının oluşturduğu çalışma sonucunda göz maskesinin uyku kalitesini önemli ölçüde arttırdığı tespit edilmiştir. [40] Uyku apnesi olan KY hastalarında vücut pozisyonunun uyku apnesi üzerindeki etkilerinin incelendiği çalışmada lateral pozisyonda uyumanın uykuda solunum olaylarının sıklığını belirgin şekilde azalttığı saptamıştır. [41] Tedavi planının ayarlanması: Sık hemşirelik girişimleri hastaların uykularının bölünmesine neden olarak uyku problemi yaşamalarına sebep olmaktadır.…”
Section: Kalp Yetersizliği Hastalarında Uyku Sorunlarının Giderilmesiunclassified